2020
DOI: 10.1016/j.ijantimicag.2020.106055
|View full text |Cite
|
Sign up to set email alerts
|

Potential of coronavirus 3C-like protease inhibitors for the development of new anti-SARS-CoV-2 drugs: Insights from structures of protease and inhibitors

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 52 publications
1
72
0
Order By: Relevance
“…Inhibition of 3CLpro: The active site of 3CLpro of SARS-CoV-2 contains Cys145 and His41 residues forming a catalytic dyad, ( He et al, 2020 ; Tahir ul Qamar et al, 2020 ) where cysteine thiol (-SH) functions as a common nucleophile (electron donating group) responsible for proteolytic cleavage ( Yang et al, 2003 ). SAR studies of pyrazolones and pyrimidines revealed that the presence of aromatic nitro (-NO 2 ) enhances cysteine protease inhibition activity, where the oxygen of the NO 2 forms a H-bond with side chains of Gly143 and Cys145, while the phenyl ring forms hydrophobic interactions ( Pillaiyar et al, 2016 ).…”
Section: Nitazoxanidementioning
confidence: 99%
“…Inhibition of 3CLpro: The active site of 3CLpro of SARS-CoV-2 contains Cys145 and His41 residues forming a catalytic dyad, ( He et al, 2020 ; Tahir ul Qamar et al, 2020 ) where cysteine thiol (-SH) functions as a common nucleophile (electron donating group) responsible for proteolytic cleavage ( Yang et al, 2003 ). SAR studies of pyrazolones and pyrimidines revealed that the presence of aromatic nitro (-NO 2 ) enhances cysteine protease inhibition activity, where the oxygen of the NO 2 forms a H-bond with side chains of Gly143 and Cys145, while the phenyl ring forms hydrophobic interactions ( Pillaiyar et al, 2016 ).…”
Section: Nitazoxanidementioning
confidence: 99%
“…To gain more insight into the effect of both propolis extract and the propolis liposomes on the inhibition of viral RNA 3CL-protease and consequently blocking viral replication, 3CL- Protease (SARS-CoV-2) Assay Kit was used ( He et al, 2020 ). 3CL-protease inhibition was tested for propolis extract, propolis liposomes, solvent of the extract (alcohol) and Remdesivir as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Significant conservation of the catalytic site has been observed between the 3CLpro structures of the SARS-CoV, MERS-CoV, and SARS-CoV-2 viruses. This discovery allows the examination of already established inhibitors of the other coronaviruses' 3CLpro enzyme, under the possibility that they may prove effective against the 3CLpro of the novel SARS-CoV-2 ( He et al, 2020 ). Furthermore, research groups have been establishing screening processes for the possible repurposing of various drugs.…”
Section: Non-structural Proteins As Potential Drug Targetsmentioning
confidence: 99%